Review of the genus Chrysoscota in Cambodia (Lepidoptera, Erebidae, Arctiinae), with description of a new species - Bayarsaikhan, Ulziijargal; Bae, Yang-Seop (Zootaxa, 2016)
The genus Chrysoscota Hampson, 1900 in Cambodia is reviewed, with description of a new species, Chrysoscota kimsuni Bayarsaikhan & Bae, sp. n. is described as new to sciences, and C. cotriangulata Holloway, 2001 is reported as new for the country. Illustrations of adults and male and female genitalia are provided for both species, with a checklist of the genus Chrysoscota.